E-cigarette use and change in plans to quit cigarette smoking among adult smokers in the United States: Longitudinal findings from the PATH Study 2014–2019. (January 2022) - Kasza, Karin A.; Edwards, Kathryn C.; Anesetti-Rothermel, Andrew; Creamer, MeLisa R.; Cummings, K. Michael; Niaura, Raymond S.; Sharma, Akshika; Pitts, Stephanie R.; Head, Sara K.; Everard, Colm D.; Hatsukami, Dorothy K.; Hyland, Andrew
Highlights: We evaluated adult daily cigarette smokers initially not planning to ever quit. Subsequent daily e-cigarette use was related to changing plans to quit smoking. E-cigarette research focused only on smokers motivated to quit limits full evaluation. Abstract: Introduction: Much of the population-based e-cigarette use and cigarette cessation literature is restricted to smokers who have expressed intention to quit smoking, though experimental studies suggest e-cigarette use might motivate some smokers to change their quit intentions. We used U.S. nationally representative data to evaluate whether e-cigarette use by smokers initially not planning to ever quit is associated with change in plans to quit. Methods: Longitudinal Population Assessment of Tobacco and Health (PATH) Study data collected between 2014 and 2019 were analyzed. Main analyses were conducted among adult daily cigarette smokers not currently using e-cigarettes with no plans to ever quit smoking (n = 2366 observations from n = 1532 individuals). Generalized estimating equations were used to evaluate the association between change in e-cigarette use and change in plans to quit smoking within the next six months, over three assessment pairs. Results: Daily cigarette smokers with no plans to quit had a higher rate of change to plan to quit if at follow-up they used e-cigarettes daily (41.4%, 95% CI: 27.1–57.3%) versus not at all (12.4%, 95% CI: 10.6–14.5%; aOR = 5.7, 95% CI: 2.9–11.2). Rate of change to plan to quit did not statistically differ between those who at follow-up used e-cigarettes some days versus not at all. Conclusions: Among adult daily cigarette smokers initially not planning to ever quit, subsequent daily e-cigarette use is associated with subsequent plans to quit smoking. Population-level research on e-cigarette use that is focused on smokers already motivated to quit may limit a complete evaluation of the smoker population.